How numbers rule the world : the use and abuse of statistics in global politics - Fioramonti, Lorenzo (Zed Books, 2014)
In this eye-opening book, Lorenzo Fioramonti provides a much-needed critique of the current 'data fever', showing both the direct consequences and indirect implications of the increasing power of numbers. At the same time, it investigates innovative attempts to resist the invasion of mainstream statistics by providing alternative measurements or rejecting quantification altogether. An innovative and timely expose? of the politics, power and contestation of numbers in everyday life